Children Victims of Murder in Samsun 1998-2007 - Aydın, Berna; Turla, Ahmet; Sataloğlu, Neva Danışkan (The Bulletin of Legal Medicine, 2009)
As a global public health problem, every kind of violence is seen all over the world. More than one million people die and much more than that are injured every year as a result of selfinfliction, interpersonal or collective violence. Children and young people are also influenced by violence. According to the data in 2000, 199.000 (9.2 in 100.000) young people are murdered, and approximately 565 children, adolescents and adults between ages 10 and 29 are reported to be dead due to violence daily. In this study, it is aimed at arriving at some implications about childhood murders by evaluating the murder cases of 0-18 age groups in Samsun provincial centre. Entries in Samsun Law Court are examined retrospectively, and data belonging to 18 murder cases of 0-18 age group committed in Centre of Samsun High Criminal Distria during 10 years (1998-2007) is evaluated. 77.8% (14/18 cases) of the cases are male and the majority of the cases (11/18 cases) are seen in 16-18 age group. The suspea is not found in two cases; but the mother in two cases, the father in one case, the friends, relatives or the neighbors in eight cases and unknown people in five cases are reached as suspects. Only in two cases the event leading to death occurred at home. Firearms or stabbing weapons are most commonly used (12/18 cases). The number of the cases in which the murdered and the suspect had an argument before the murder is 11. As individuals and society, it is vital that we take the essential precautions and that we must strive for diminishing the social violence to protect the child’s right to live and to lead his/ her life healthily. Key words: Childhood, murder